Karakteristik Sebaran Lokasi Warung Sembako Di Jalan Sekumpul Martapura :Tinjauan Teori Lokasi - Bulan, Siti (PPJP ULM, 2024)
Data analysis techniques to be used in this study using descriptive analysis. The subjects in this study 42 basic food stalls. The findings obtained spatially of the distribution of basic food stalls on Jalan Sekumpul spread along the main road and Ar-Raudhah Mosque. Based on this map, the characteristics of the distribution of basic food stalls are in accordance with the location theory. The distance between the Grocery Stalls and the Ar-Raudhah Sekumpul Mosque in this research data has minimum (127.87 m), maximum (11,490 m), average (667.68 m), median (295.11) and standard deviation ( 1729.12). These findings show that the location of the distribution of basic food stalls on Jalan Sekumpul tends to be in accordance with the location theory.